Peran Guru Bimbingan Konseling dalam Menanggulangi Perilaku Menyontek Siswa di SMP Negeri Kota Padang - Ananda Maha Putri; Nur Syahadani Putri (Universitas PGRI SUMATERA BARAT, 2023)
The background of this research is the occurrence of cheating behavior by students, when carrying out exams on average in each class there are 5-15 students who cheat, and during the midterm exam implementation there are 65% -80% of students cheating. The supervising teacher is one of the educators who plays a role in tackling students' cheating behavior at school. This study aims to describe the role of the supervising teacher in overcoming student cheating behavior, namely with regard to: (1) the role of the supervising teacher in preventing the occurrence of cheating behavior in students, (2) the role of the supervising teacher in alleviating cheating behavior in students. This research is classified as a quantitative descriptive research, namely describing a certain situation or situation as it is. The population in this study were supervising teachers at State Junior High Schools in Padang City. Sampling used the Cluster Sampling method, which consisted of 20 supervising teachers. The data collection tool used was a questionnaire and the data were analyzed using percentage techniques. Based on this research, it is suggested: (1) supervising teachers, in order to further improve the services that will be provided to students so that students do not have cheating behavior, (2) subject teachers, it is expected that teachers pay more attention to student learning processes and work together with supervising teachers to overcome behavior cheating students, and (3) it is expected that other researchers will continue research on the collaboration of supervising teachers with school personnel to overcome student cheating behavior. Keywords: The role of guidance counseling teachers, cheating behavior.